2012
DOI: 10.1097/mlr.0b013e31826410fb
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Measuring Culturally Competent Care

Abstract: Background Providing culturally competent care shows promise as a mechanism to reduce healthcare inequalities. Until the recent development of the CAHPS Cultural Competency Item Set (CAHPS-CC), no measures capturing patient-level experiences with culturally competent care have been suitable for broad-scale administration. Methods We performed confirmatory factor analysis and internal consistency reliability analysis of CAHPS-CC among patients with type 2 diabetes (n=600) receiving primary care in safety-net … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The CAHPS-CC® is noted to be a valid and reliable scale for assessing culturally competent care from the patient perspective (Stern et al, 2012;Weech-Maldonado et al, 2012). Weech-Maldonado et al (2012) confirmed the internal consistency of the original seven-factor CAHPS-CC® scale using Cronbach alphas, as well as its validity using exploratory and confirmatory factor analysis, multitrait scaling analysis, and regression analysis.…”
Section: Variable Definitions and Instrumentationmentioning
confidence: 65%
See 1 more Smart Citation
“…The CAHPS-CC® is noted to be a valid and reliable scale for assessing culturally competent care from the patient perspective (Stern et al, 2012;Weech-Maldonado et al, 2012). Weech-Maldonado et al (2012) confirmed the internal consistency of the original seven-factor CAHPS-CC® scale using Cronbach alphas, as well as its validity using exploratory and confirmatory factor analysis, multitrait scaling analysis, and regression analysis.…”
Section: Variable Definitions and Instrumentationmentioning
confidence: 65%
“…Research has largely assessed health care providers' own perceptions of cultural competence and therefore offering biased judgments of self-perceived knowledge, skills, and attitudes (Kirmayer, 2012). This has slowed the development of patient-centered strategies aimed at improving the delivery of high-quality care (Stern et al, 2012). Understanding patients' perceptions of cultural competence is essential to improving engagement in health care services and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We expect an increase in satisfaction scores before and after the education sessions by 10% in post-HKTP based on prior studies [ 98 ]. Differences in CAHPS composite scores will then be compared between pre- and post-HKTP by each site using a two-sample t-test.…”
Section: Methods and Designmentioning
confidence: 99%
“…(4) We present the three CAHPS-CC domains that were psychometrically sound among both English and Spanish speakers in our participant population. (2) These domains include Doctor Communication - Positive Behaviors (5 items), Doctor Communication - Health Promotion (4 items), and Trust (5 items).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to examine the Doctor Communication – Positive Behaviors, Doctor Communication – Health Promotion, and Trust domains because these domains had acceptable psychometric properties in our participant sample based on the authors’ previous work. (2) The Doctor Communication – Positive Behaviors and Doctor Communication – Health Promotion domains measure aspects of patient-provider communication. Items in the Doctor Communication – Positive Behaviors domain ask patients the extent to which their provider exhibited various aspects of good communication, including explaining things in a way that is easy to understand, listening carefully, spending adequate time with you, and showing respect.…”
Section: Introductionmentioning
confidence: 99%